The Changing Landscape of Antibiotic Treatment: Reevaluating Treatment Length in the Age of New Agents - Francesca Serapide; Salvatore Rotundo; Luca Gallelli; Caterina Palleria; Manuela Colosimo; Sara Palma Gullì; Gianmarco Marcianò; Alessandro Russo (Antibiotics)
Background: The landscape of antimicrobial therapy is undergoing a profound transformation; the contemporary arsenal of antimicrobials, particularly those with extended half-lives and enhanced tissue penetration, necessitates critically reassessing these traditional paradigms. The growing emphasis on antimicrobial stewardship programs has underscored the importance of optimizing antimicrobial agents to minimize the development and spread of resistance. Shorter treatment durations, when clinically appropriate, represent a key strategy in this endeavor. Methods: This narrative review provides a comprehensive synthesis of current evidence on the duration of antimicrobial therapy, with a particular focus on the clinical and pharmacological implications of novel agents, including long-acting formulations. Results: We critically examine the pharmacokinetic and pharmacodynamic properties of these agents, evaluate the opportunities and limitations associated with treatment shortening strategies, and underscore the pivotal role of antimicrobial stewardship in optimizing therapeutic outcomes within an increasingly complex and evolving landscape. Conclusions: The future of antimicrobial therapy lies in a personalized approach, where treatment decisions are tailored to the individual patient, but detailed clinical trials are necessary to evaluate these approaches.